A Systematic Review of Anticoagulation Strategies for Patients with Atrial Fibrillation in Critical Care - Nelson, Alexandra Jayne; Johnston, Brian W.; Waite, Alicia Achiaa Charlotte; Lemma, Gedeon; Welters, Ingeborg Dorothea (Thrombosis and Haemostasis, 2021)
Background Atrial fibrillation (AF) is the most common cardiac arrhythmia in critically ill patients. There is a paucity of data assessing the impact of anticoagulation strategies on clinical outcomes for general critical care patients with AF. Our aim was to assess the existing literature to evaluate the effectiveness of anticoagulation strategies used in critical care for AF.Methods A systematic literature search was conducted using MEDLINE, EMBASE, CENTRAL, and PubMed databases. Studies reporting anticoagulation strategies for AF in adults admitted to a general critical care setting were assessed for inclusion.Results Four studies were selected for data extraction. A total of 44,087 patients were identified with AF, of which 17.8 to 49.4% received anticoagulation. The reported incidence of thromboembolic events was 0 to 1.4% for anticoagulated patients, and 0 to 1.3% in nonanticoagulated patients. Major bleeding events were reported in three studies and occurred in 7.2 to 8.6% of the anticoagulated patients and in up to 7.1% of the nonanticoagulated patients.Conclusion There was an increased incidence of major bleeding events in anticoagulated patients with AF in critical care compared with nonanticoagulated patients. There was no significant difference in the incidence of reported thromboembolic events within studies between patients who did and did not receive anticoagulation. However, the outcomes reported within studies were not standardized, therefore, the generalizability of our results to the general critical care population remains unclear. Further data are required to facilitate an evidence-based assessment of the risks and benefits of anticoagulation for critically ill patients with AF.
Keywords: atrial fibrillation; anticoagulation; critical care; intensive care; new-onset AF